Ion channels. Issue 10 (5th April 2013) - Bradding, Peter; Wulff, Heike
Abstract : Effective therapies for the 10% of patients with 'severe' asthma remain elusive, while other pulmonary diseases such as idiopathic pulmonary fibrosis are currently untreatable. Many cellular processes rely heavily on signals delivered by changes in the intracellular-free Ca 2+ concentration, in many cases relying on Ca 2+ influx from the extracellular fluid through specific ion channels. This Ca 2+ influx is, to some extent, dependent on the plasma membrane potential, which is controlled by the flow of other ions such as K + and Cl − through their own channels. Irrespective of the point from where pathophysiological cell function is sustained, all mechanisms are predicted to rely heavily on the activity of the final effector ion channels required for pathological cell function. Ion channels are therefore highly attractive targets for the treatment of many diverse diseases, including those affecting the lung.